2015
DOI: 10.1099/vir.0.000085
|View full text |Cite
|
Sign up to set email alerts
|

Permissivity of primary hepatocytes and hepatoma cell lines to support hepatitis C virus infection

Abstract: The major cell type supporting hepatitis C virus (HCV) infection is the hepatocyte; however, most reports studying viral entry and replication utilize transformed hepatoma cell lines. We demonstrate that HCV pseudoparticles (HCVpp) infect primary hepatocytes with comparable rates to hepatoma cells, demonstrating the limited variability in donor hepatocytes to support HCV receptor-glycoprotein-dependent entry. In contrast, we observed a 2-log range in viral replication between the same donor hepatocytes. We not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…While some groups have reported successful culture of patient-derived HCV, these methods generally exhibit poor replication efficiency and therefore do not represent a tractable means of predicting neutralization sensitivity in vivo ; instead, surrogate models, such as the HCVpp system or chimeric HCVcc, have proven to be more robust tools (reviewed in reference 42 ). Previous studies on antibody neutralization have used the cell line Huh7.5 ( 40 ) or primary hepatocytes ( 43 ); we chose the former, as that cell line is more amenable and the HCV entry process is comparable to that observed in primary hepatocytes ( 44 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…While some groups have reported successful culture of patient-derived HCV, these methods generally exhibit poor replication efficiency and therefore do not represent a tractable means of predicting neutralization sensitivity in vivo ; instead, surrogate models, such as the HCVpp system or chimeric HCVcc, have proven to be more robust tools (reviewed in reference 42 ). Previous studies on antibody neutralization have used the cell line Huh7.5 ( 40 ) or primary hepatocytes ( 43 ); we chose the former, as that cell line is more amenable and the HCV entry process is comparable to that observed in primary hepatocytes ( 44 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of the parameters defining infectious HCV in humans is incomplete due to the limited replication of primary HCV strains in any in vitro model system ( 56 , 57 ). Previous studies have reported on the infectivity of patient-derived sera in chimpanzees ( 34 ) and humanized uPA-SCID mice ( 42 , 54 , 58 ), however, these studies were limited by the small number of clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of the parameters de ning infectious HCV in man is incomplete due to the limited replication of clinical or primary HCV strains in in vitro model systems (50,51). Previous studies have reported on the infectivity of patient-derived sera in chimpanzees (32) and humanized uPA-SCID mice (39,44,52), however, these studies were limited by the small number of clinical samples studied.…”
Section: Discussionmentioning
confidence: 99%